Interfacial engineering of Bi2S3/Ti3C2T x MXene based on work function for rapid photo-excited bacteria-killing - Jianfang Li; Zhaoyang Li; Xiangmei Liu; Changyi Li; Yufeng Zheng; Kelvin Wai Kwok Yeung; Zhenduo Cui; Yanqin Liang; Shengli Zhu; Wenbin Hu; Yajun Qi; Tianjin Zhang; et al. (Nature communications, 2021)
MXenes have emerged as potential antimicrobial materials. Here, the authors report on the creation of a Schottky junction to increase the charge separation between MXenes and semiconductor to increase photodynamic creation of reactive oxygen species under near infrared irradiation for antibacterial purposes.